Floristic changes at Khersan Glacier Territory, Alamkuh Mountain, Central Alborz, North of Iran - KOUROSH KAVOUSI; TAHER NEJADSATARI; YUNES ASRI; HAMID EJTEHADI; RAMEZAN ALI KHAVARI-NEJAD (Biodiversitas Journal of Biological Diversity, 2016)
Kavousi K, Nejadsattari T, Asri Y, Ejtehadi H, Khavari-Nejad RA. 2016. Floristic changes at Khersan Glacier Territory,Â Alamkuh Mountain, Central Alborz, North of Iran. Biodiversitas 17: 11-15. Extensive investigation in subnival-nival area aroundKhersan glacier moraine introduced 71 vascular plant species. From this list 43 species have been listed in Noroozi et al. (2011) in â€œsubnival-nival vascular plant species of Iran : a unique high mountain flora and its threat from climate warmingâ€ and the others are new for subnival-nival area of Iran. Among this plant list 31 species had introduced with Kotschy (1861a.), Bornmuller Â (1906), Melchior (1937), Klein (1982),Â  European researchers and the other is named for the first time from Khersan glacier territory. Many species suchas Astragalus macrosemius, Pseudocamelina kleinii, Crepis multicaulis subsp. congesta, Didymophysa fedtschenkoana and Drabamelanopus due to glacier condition have very sensitive habitat, vulnerable and only gathered from restrict area with conservation value.Vegetation change happened in many nival and subnival areas with upward movement in the same habitat and movement from loweraltitude at alpine towards summit in subnival and nival. Carex oreophila, Campanula stevenii, Bromus brachystachyus, Oxytropisimmersa, Erigeron uniflorus, Trachydium pauciradiatum, Scorzonera radicosa and some other species are surprisingly movement tosubnival area and many nival and subnival species such as Didymophysa aucheri, Didymophysa fedtschenkoana, Dracocephalumaucheri and Arabis caucasica have come significantly upward in nival. The movement is different in all side of Khersan glacier morainein north, south and the east (besise moraineÂ tongue) slops and limited with presence of soil natural generation and other ecological remarks. Limitation for soil generation starts at different altitude in northern, southern and eastern slopes of Khersan glacier valley. This study examined changes of flora in Khersan glacier territory during recent decades according to extensive data gathering, full list of Khersan glacier territory introduced Barbarea stricta, Draba melanopus, Pseudocamelina kleinii, Crepis multicaulis subsp. congesta as new report for flora of Iran and flora Iranica area.